Comparative Efficacy, Safety, and Patient Preference of One-Month (1HP) versus Three-Month (3HP) Rifapentine-Based Regimens for Latent Tuberculosis: A Network Meta-Analysis of HIV, Silicosis, and General Risk Populations - Muhammad Ridwan; Roza Kurniati; Fauzar (HM Publisher, 2026)
Background: The programmatic management of latent tuberculosis infection (LTBI) is undergoing a paradigm shift from long-course isoniazid monotherapy to short-course rifamycin-based regimens. While the 3-month weekly rifapentine/isoniazid (3HP) regimen is well-established, the ultra-short 1-month daily rifapentine/isoniazid (1HP) regimen offers a potential advancement in adherence. However, concerns regarding systemic hypersensitivity reactions, hepatotoxicity mechanisms, and efficacy in non-HIV populations like silicosis remain. Methods: We conducted a systematic review and network meta-analysis (NMA) utilizing a random-effects frequentist model. We executed a comprehensive search of MEDLINE, Embase, and Cochrane Central Register of Controlled Trials to identify randomized controlled trials comparing rifapentine-based regimens. We analyzed data comprising over 10,000 participants to evaluate the efficacy (prevention of active TB), safety (hepatotoxicity and hypersensitivity), and completion rates of 1HP, 3HP, 4-month rifampin (4R), and 9-month isoniazid (9H). We specifically integrated novel data on silicosis patients and patient preference metrics. Results: The network analysis demonstrated that 1HP was non-inferior to 9H in preventing active tuberculosis (Incidence Rate Difference: -0.02 per 100 person-years). 1HP achieved the highest treatment completion rate (97%), significantly superior to 3HP (82%) and 9H (69%). Safety analysis revealed a distinct divergence: 3HP was associated with a higher incidence of systemic flu-like drug reactions (3.5%) compared to 9H (0.4%), whereas 1HP demonstrated a safety profile that minimized both the hepatotoxicity of isoniazid and the hypersensitivity of intermittent rifapentine. In silicosis patients, modified 1-month regimens proved safe. However, preference analysis indicated that 81% of patients preferred the weekly dosing of 3HP over the daily burden of 1HP. Conclusion: 1HP represents the most effective strategy for maximizing treatment completion without compromising bactericidal activity. The daily dosing of 1HP appears to induce immune tolerance, mitigating the hypersensitivity reactions observed in weekly 3HP dosing. While 3HP remains a viable option for those preferring less frequent dosing, 1HP is the superior clinical recommendation for rapid sterilization of latent reservoirs.